Efforts of Bhabinkamtibmas in Preventing the Criminal Act of Togel Gaming in the Jurisdiction of the Kebumen Police - Capa Togatorop, Christopher Juan; S, Basir; Nita, Surya (Journal Research of Social Science, Economics, and Management, 2022)
The law must be enforced to achieve the goals and ideals of the Indonesian nation as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia. This study aims to find out what efforts have been made by Bhabinkamtibmas in preventing the crime of lottery gambling in Kebumen . And what is the general situation of the Kebumen Regency and know what factors support and hinder Bhabinkamtibmas in preventing the occurrence of lottery gambling crimes in the jurisdiction of the Kebumen Police. The method used in method used is through interviews, observation, and library research. Data analysis using qualitative data analysis. The results obtained can be said to be not optimal because of the factors that might hinder the performance of Bhabinkamtibmas. Inhibiting factors include the lack of public awareness of the law, so many are still afraid of the police, then the lack of personnel in the field which makes Bhabinkamtibmas members have to hold concurrent positions. In addition to inhibiting factors, there are also supporting factors that help Bhabinkamtibmas in carrying out their duties, there is budget support for Bhabinkamtibmas, making additions to optimize Bhabinkamtibmas activities in the field, maximizing breakthroughs from the Kebumen Police Chief which makes Awards & Punishments for Bhabinkamtibmas members to encourage them to carry out their duties in the field so that its performance can be optimal.